The impact of the social level of the employee of Asnan Medical Limited Company on reducing the cost of applying the overall quality standards in work - Sudan - Awadallah, Ahmed Hassan Abdel Qader; Ibrahim, Mohammed Al Moataz Mojtabe (Arab Journal for Sciences and Research Publishing, 2016)
The study aims in general to review relevant previous studies, the concept of social levels and lifestyle and how to measure and knowing, the concept of quality and total quality management and quality costs, and the importance of accounting information systems for the cost of quality, the study was based on the theory that lack of interest in social background and level of living of the individual has a significant impact on the level of the rehabilitation of the individual to apply the standards of quality and that the report accounting information systems on quality costs cannot be the management to identify the quality and reduce their costs (quality costs). The study used the analytical descriptive approach through a review of books and periodicals related to its subject. And the questionnaire was the tool of the study that distributed on several levels of social and administrative and scientific and collect information through social diversity. The study showed a number of results, the most important of them were: there is a statistical significance that families with a high standard of living give their members self-confidence and make the individual more solid in the face of mistakes in his working life and accept criticism and turn it into a positive motivation and achieve successes in his work Unlike the individual who comes from a simple social environment and has a weak and shaky personality, he does not accept any criticism and does not seek reforms, but often he is content to hide his mistakes. There is also a statistical significance that the individual coming from a high social level has a strong and influential leadership personality stemming from his confidence in himself as opposed to that coming from a simple social background.
Keywords: social level; employee; The standard of living of the employee; Its impact on its application of quality standards; quality standards